Green Hostel: uma hospedagem alternativa no Parque Estadual do Jalapão – Tocantins - Raposo, Bárbara Martins (Universidade Federal do Tocantins, 2020)
This final graduation paper presents the architectural project of a Hostel in the city of Mateiros, located in the Jalapão State Park, in Tocantins. This type of alternative accommodation brings lower prices to it’s guests by offering shared spaces such as dorms, bathrooms, kitchen and recreation areas. To bring a truthful and human interaction with the place and it’s locals, this building was designed with shared and accessible spaces to promote cultural exchanges and interaction with the local nature by it’s structure, ensuring comfort and sustainability.